Gameplay Engagement and Learning in Game-Based Learning: A Systematic Review. (December 2015) - Abdul Jabbar, Azita Iliya; Felicia, Patrick
In this review, we investigated game design features that promote engagement and learning in game-based learning (GBL) settings. The aim was to address the lack of empirical evidence on the impact of game design on learning outcomes, identify how the design of game-based activities may affect learning and engagement, and develop a set of general recommendations for GBL instructional design. The findings illustrate the impact of key gaming features in GBL at both cognitive and emotional levels. We also identified gaming trends and several key drivers of engagement created by the gaming features embedded within GBL, as well as external factors that may have influences on engagement and learning.